PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DAN PENGEMBANGAN OBJEK WISATA PULAU TABALINGE KABUPATEN PULAU MOROTAI - Rasyid, Rusman; Purwati, Endang; Agustang, Andi Tenri Pada; Lutfi, Nurhalisa J (Universitas Negeri Makassar, 2023)
This paper attempts to provide an overview of the main findings and conclusions of the research conducted. The primary objective of this study is to provide a systematic, accurate, and impartial description of how the public participates in the oversight and growth of tourism attractions on Tabalinge Island, located in the Morotai Island geographical area. The research methodology employed in this study is qualitative descriptive research, which involves the collection of data through observations, interviews, and documentation. The findings of this study indicated that the general public did not engage directly in the initial planning stage of the management and development of Tabalinge Island as a destination for tourists. Rather, their involvement was observed to be limited to providing feedback and suggestions during public consultations held after the initial planning stage. This lack of direct engagement from the general public may have resulted in disconnect between the tourism attractions offered on Tabalinge Island and the preferences and needs of potential tourists. Additionally, it highlights the importance of incorporating community input and involvement in future management and development plans to ensure a more inclusive and sustainable tourism destination. During the subsequent implementation phases of management and service provision, which followed a top-down approach encompassing both tangible and intangible aspects, in the phase of evaluation and monitoring, there is restricted public participation in preventive measures aimed at mitigating security and order disruptions. This involvement primarily entails the dissemination of information, with the public acting as passive recipients of government updates regarding surveillance efforts. However, opportunities for public feedback are not provided.